2011
DOI: 10.1099/jmm.0.029140-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for AmpC β-lactamase detection in Enterobacteriaceae

Abstract: AmpC b-lactamases (Bla AmpC ) are an emerging group of antimicrobial resistance determinants. The lack of an agreed Bla AmpC detection method hinders investigation of their epidemiology and understanding of their clinical significance. This study compared the sensitivity and specificity of phenotypic methods of Bla AmpC detection in a collection of 246 Enterobacteriaceae with a diverse range of b-lactam resistance profiles. The Bla AmpC screening methods evaluated were based on cephamycin, ceftazidime and cefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 30 publications
6
50
3
3
Order By: Relevance
“…As well as Brilliance ESBL agar screening, the presence of ESBL-or AmpC-type resistance was confi rmed or excluded by the commercial ABCD test kit Mast ID D68C (Mast Diagnostic, Amlens, France) as described by the manufacturer and others [17]. In addition, resistance testing was performed via E-tests (BioMerieux, Marcy-l'Étoile, France) for piperacillin, ceftazidime, ciprofl oxacin, and meropenem as representatives of the four important bactericidal antibiotic substance groups of penicillins, cephalosporins, fl uoroquinolones, and carbapenems, respectively.…”
Section: Assessment Of Isolated Strainsmentioning
confidence: 99%
“…As well as Brilliance ESBL agar screening, the presence of ESBL-or AmpC-type resistance was confi rmed or excluded by the commercial ABCD test kit Mast ID D68C (Mast Diagnostic, Amlens, France) as described by the manufacturer and others [17]. In addition, resistance testing was performed via E-tests (BioMerieux, Marcy-l'Étoile, France) for piperacillin, ceftazidime, ciprofl oxacin, and meropenem as representatives of the four important bactericidal antibiotic substance groups of penicillins, cephalosporins, fl uoroquinolones, and carbapenems, respectively.…”
Section: Assessment Of Isolated Strainsmentioning
confidence: 99%
“…Antimicrobial resistance among Enterobacteriaceae is fast becoming a worldwide public health concern, and AmpC blactamases are an emerging group of antimicrobial resistance determinants [13]. The occurrence of ampC genes on plasmids presents a great challenge to infection control because plasmidmediated genes can spread to other organisms within a hospital or geographic region.…”
Section: Discussionmentioning
confidence: 99%
“…Ingram et al, (2011) demonstrated that 72/74 PCR-positive Enterobacteriaceae isolates showed resistance to cefoxitin with a sensitivity of 97%, and a specificity of 64%.…”
Section: Screening For Ampc Production By Fox Disk Diffusion Methods (Dd)mentioning
confidence: 99%
“…Also, Peter-Getzlaff et al, (2011) demonstrated that CC-DD test correctly detected 20/21 (95.2%) AmpC (chromosomal and plasmid-mediated) positive E. coli strains by PCR and did not give false-positive results when using the same concentration and the same cutoff. Ingram et al, (2011) demonstrated that the sensitivity and specificity of CC-DD test when using cloxacillin (100µg) were 53% and 99% respectively for detection of AmpC production. The sensitivity and specificity were improved to (70% and 100%) respectively when using cloxacillin (200µg).…”
Section: Cloxacillin Combined Disk Diffusion Test (Cc-dd)mentioning
confidence: 99%
See 1 more Smart Citation